A micro-funded theory of multilateral resistance to migration - Léa Marchal; Claire Naiditch (Kiel Institute for the World Economy (IfW), 2016)
This paper provides a micro-funded theory of multilateral resistance to migration analyzing how financial constraints determine migration trends. We build a RUM model in which we explicitly introduce the budget constraint in the migration decision: individuals cannot afford migrating to a destination for which the migration cost (which depends on the immigration policy of the destination country) is higher than their current income. We find that the migration rate between two countries depends on the characteristics of the origin and destination countries and their relative accessibility, and also on a budget constraint term. This term depends on the attributes of alternative destinations. Thus, the model exhibits multilateral resistance to migration. We perform a numerical analysis based on 23 European countries in 2008 and evidence multilateral resistance to migration induced by the implementation of intra-EU migration restrictions following the 2004 EU enlargement.
Keywords: F22; J61; O15; C63; 330; Migration; Budget constraint; Immigration policy; RUM model; Multilateral resistance to migration